Household expenditure on cigarettes and tobacco in Syria - Ahmad Alachkar (University of Kent, Department of Economics, 2008)
The study uses average data from Household Income and Expenditure Survey 2004 in Syria to examine monthly household expenditure on cigarettes and tobacco and its relationships with a group of socioeconomic variables. It is found that this expenditure increases by average household income. This increase, however, is relatively small; the percent of total expenditure allocated to smoking is much higher among the poor compared to the rich. Expenditure on smoking is negatively affected by the improvements in educational conditions. Household expenditure on domestic cigarettes does not vary by household income; it is positively correlated with characteristics of the place of residence, particularly with illiteracy, polygamy; and negatively with developed educational structure. Expenditure on foreign cigarettes is spread mostly in governorate centers and among rich households. The study deduces that people with low income cannot smoke unless they decrease their monthly expenditure on basic requirements. In order to decrease smoking, two recommendations are made, developing the educational structure and eradicating illiteracy and launching concentrated campaigns to raise awareness against smoking.
Keywords: C21; D12; 330; household economics; social policy; poverty; Verbraucherausgaben; Zigarette; Tabak; Syrien